If it's not what You are looking for type in the equation solver your own equation and let us solve it.
147=-3x-3(-5x-5)
We move all terms to the left:
147-(-3x-3(-5x-5))=0
We calculate terms in parentheses: -(-3x-3(-5x-5)), so:We get rid of parentheses
-3x-3(-5x-5)
We multiply parentheses
-3x+15x+15
We add all the numbers together, and all the variables
12x+15
Back to the equation:
-(12x+15)
-12x-15+147=0
We add all the numbers together, and all the variables
-12x+132=0
We move all terms containing x to the left, all other terms to the right
-12x=-132
x=-132/-12
x=+11
| 7=-8r | | -5b-7=93 | | X^4+675=84x^2 | | X-67=-11(2x+4) | | -38=2n-6 | | -2+13.8x=-8x-(6x+1) | | I5x=-9 | | x+.06x=50.97 | | I5x=12 | | v+2.63=4.36 | | 9-8a=1 | | 15d-4=19 | | 4(-1x-5)=-4 | | 6x+23=7x+15 | | 10m+5=35 | | 720*1/x+1.25x=718.75 | | -1-k=1 | | 0.6(x+38000)=51000 | | 5(-4x-2)=-210 | | 5/8(20.8)+0y=13 | | 5/8(20.8)+y0=13 | | 12x-8-(5x+2)=67 | | 6=u/3 | | 6(-9+4x)=-126 | | W(x+3)+5x=34 | | 3x+27=4x+12 | | 2(1x-10)=2 | | -2(7x-7)=-42 | | 3x+16=4x-2 | | 7x-9=106 | | 4(2-x)=-32 | | 6x+4=184 |